Inovasi Desain Pembelajaran Pendidikan Agama Islam Dalam Meningkatkan Keterlibatan Siswa dan Guru - Muhammad Yusron Maulana El-Yunusi; Zidni Akholik Almaghfiroh (Departement of Mathematics Education, 2024)
This article discusses the application of innovation in Islamic Religious Education (PAI) learning design with the aim of increasing student and teacher involvement in the learning process. Through an approach that focuses on the use of modern technology, project-based learning methods, and the use of engaging multimedia resources, learning designs can be designed to provide interactive and relevant learning experiences for PAI students.The importance of student involvement in PAI learning is emphasized in this article, where students are encouraged to be actively involved in discussions, group work, and personal reflection on the material being taught. This aims to increase their understanding of the religious concepts and values ​​taught in this subject. Apart from that, the role of teachers as effective learning facilitators is also emphasized in this learning design innovation. Teachers are expected to play a more proactive role in motivating students, helping them explore and apply religious values ​​in the context of everyday life.Overall, this article presents ideas about how PAI learning design innovations can be an effective means of increasing student and teacher engagement, as well as increasing the effectiveness of learning in religious subjects. Thus, it is hoped that this article can make a positive contribution in efforts to improve religious education in the school environment.